2016
DOI: 10.1109/tpami.2015.2496269
|View full text |Cite
|
Sign up to set email alerts
|

SALSA: A Novel Dataset for Multimodal Group Behavior Analysis

Abstract: Studying free-standing conversational groups (FCGs) in unstructured social settings (e.g., cocktail party ) is gratifying due to the wealth of information available at the group (mining social networks) and individual (recognizing native behavioral and personality traits) levels. However, analyzing social scenes involving FCGs is also highly challenging due to the difficulty in extracting behavioral cues such as target locations, their speaking activity and head/body pose due to crowdedness and presence of ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 71 publications
0
99
0
Order By: Relevance
“…[5] studied lexical cues from informal texts for recognizing personalities. [6] showed a high correlation of personality with non-verbal behavioral measures such as the amount of speech and physical activity. [7] investigated the physiological correlation of emotion and personality using commercial sensors and found that the emotion-to-personality relationship is better captured by non-linear rather than linear statistics.…”
Section: Introductionmentioning
confidence: 99%
“…[5] studied lexical cues from informal texts for recognizing personalities. [6] showed a high correlation of personality with non-verbal behavioral measures such as the amount of speech and physical activity. [7] investigated the physiological correlation of emotion and personality using commercial sensors and found that the emotion-to-personality relationship is better captured by non-linear rather than linear statistics.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiment, we used the SALSA dataset Cocktail Party Sequence, which was created by Alameda et al [4]. This dataset records the social interactions among 18 participants in an indoor environment for 500 frames, and is annotated with information about each individual's location, body orientation and group membership.…”
Section: Methodsmentioning
confidence: 99%
“…Availability of a large-scale dataset is essential to computationally investigate the nonverbal communication in a data-driven manner. Despite existing datasets that provide measurements for human motion and behaviors [10,38,74,13,2,30], there is no dataset that satisfies the following core requirements for understanding nonverbal human behaviors: (1) capturing 3D full body motion with a broad spectrum of nonverbal cues (including face, body, and hands); (2) capturing signals of naturally interacting groups (more than two people to include attention switching); and (3) collecting the data at scale. The limited availability of datasets motivates us to build a new dataset that contains social interactions among hundreds of interacting groups with a broad spectrum of 3D body motion measurements.…”
Section: Triadic Interaction Dataset With Fullspectrum Social Signal mentioning
confidence: 99%
“…Social Signal Dataset: How to measure and collect nonverbal signal data is important to pursue a data-driven approach for our goal. However, only few datasets contain socially interacting group motion [2,42,37,58]. The scenes in these datasets are often in a table setup, limiting free body movement and capturing the upper-body only.…”
Section: Introductionmentioning
confidence: 99%